Lipophilic oligonucleotides spontaneously insert into lipid membranes, bind complementary DNA strands, and sequester into lipid-disordered domains - Bunge, Andreas (Langmuir : the ACS journal of surfaces and colloids, 2007)
For the development of surface functionalized bilayers, we have synthesized lipophilic oligonucleotides to combine the molecular recognition mechanism of nucleic acids and the self-assembly characteristics of lipids in planar membranes. A lipophilic oligonucleotide consisting of 21 thymidine units and two lipophilic nucleotides with an alpha-tocopherol moiety as a lipophilic anchor was synthesized using solid-phase methods with a phosphoramadite strategy. The interaction of the water soluble lipophilic oligonucleotide with vesicular lipid membranes and its capability to bind complementary DNA strands was studied using complementary methods such as NMR, EPR, DSC, fluorescence spectroscopy, and fluorescence microscopy. This oligonucleotide inserted stably into preformed membranes from the aqueous phase. Thereby, no significant perturbation of the lipid bilayer and its stability was observed. However, the non-lipidated end of the oligonucleotide is exposed to the aqueous environment, is relatively mobile, and is free to interact with complementary DNA strands. Binding of the complementary single-stranded DNA molecules is fast and accomplished by the formation of Watson-Crick base pairs, which was confirmed by 1H NMR chemical shift analysis and fluorescence resonance energy transfer. The molecular structure of the membrane bound DNA double helix is very similar to the free double-stranded DNA. Further, the membrane bound DNA double strands also undergo regular melting. Finally, in raft-like membrane mixtures, the lipophilic oligonucleotide was shown to preferentially sequester into liquid-disordered membrane domains